2021
DOI: 10.3390/catal11050535
|View full text |Cite
|
Sign up to set email alerts
|

Core-Shell ZnO@Cu2O as Catalyst to Enhance the Electrochemical Reduction of Carbon Dioxide to C2 Products

Abstract: The copper-based catalyst is considered to be the only catalyst for electrochemical carbon dioxide reduction to produce a variety of hydrocarbons, but its low selectivity and low current density to C2 products restrict its development. Herein, a core-shell xZnO@yCu2O catalysts for electrochemical CO2 reduction was fabricated via a two-step route. The high selectivity of C2 products of 49.8% on ZnO@4Cu2O (ethylene 33.5%, ethanol 16.3%) with an excellent total current density of 140.1 mA cm−2 was achieved over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The Cu-ZnO presents even faster kinetics for the CO formation, even though this catalyst also favors the *OCHO formation path . The Cu-ZnO GDE exhibits the highest internal exchange current density, associated with the lowest overpotential that Cu-ZnO structures are reported to induce for the ECR , and the contribution of Cu in CO formation . For the rest of the heterostructured GDEs, the slower kinetics are attributed to the enhanced HER rate arising from the exposed d-block metallic centers.…”
Section: Resultsmentioning
confidence: 98%
“…The Cu-ZnO presents even faster kinetics for the CO formation, even though this catalyst also favors the *OCHO formation path . The Cu-ZnO GDE exhibits the highest internal exchange current density, associated with the lowest overpotential that Cu-ZnO structures are reported to induce for the ECR , and the contribution of Cu in CO formation . For the rest of the heterostructured GDEs, the slower kinetics are attributed to the enhanced HER rate arising from the exposed d-block metallic centers.…”
Section: Resultsmentioning
confidence: 98%
“…(b) FE of products on ZnO@4Cu 2 O; (c) the total current density of products on xZnO@yCu 2 O catalysts. 165 Copyright 2021. MDPI.…”
Section: The Zno-based Catalystsmentioning
confidence: 99%
“…The introduction of GN was one of the effective methods to produce C 3 products from CO 2 , while tuning the structure of ZnO/Cu 2 O could also enhance the electrochemical reduction of CO 2 to C 2 products. For example, a catalyst with a ZnO core and a Cu 2 O shell was fabricated using a wet chemical method by Zhu et al 165 With the ZnO@4Cu 2 O catalyst, it was possible to make CO 2 firstly generate CO at the ZnO sites, and then the CO was coupled on to Cu 2 O to generate the C 2 products. By tailoring the synergy of the Cu and Zn oxides, a high FE of 49.8% was obtained for the C 2 products (ethylene: 33.5%, ethanol: 16.3%, as shown in Fig.…”
Section: The Zno-based Catalystsmentioning
confidence: 99%
“…Their excellent electrochemical reduction of CO 2 was attributable to the core-shell structure and the enhanced kinetics for the formation of ethylene and ethanol. 48 Deo et al used a two-step chemical process to fabricate a heteronanobrush assembly (ZnO NRs grown on Cu 2 O nanoneedles) on a Cu substrate, and the sample exhibited enhanced field emission and photodegradation. 49 Kathalingam et al reported the hydrothermal fabrication of n-ZnO NRs on electrodeposited p-Cu 2 O films and studied the photosensing response of metallic -contact (Ag/ZnO NRs/Cu 2 O/ITO) and sandwich-type (ITO/ZnO NRs/Cu 2 O/ITO) devices.…”
Section: Introductionmentioning
confidence: 99%
“…employed a sol–gel method and an epitaxial shell growth approach to fabricate ZnO−Cu 2 O catalysts. Their excellent electrochemical reduction of CO 2 was attributable to the core‐shell structure and the enhanced kinetics for the formation of ethylene and ethanol 48 . Deo et al.…”
Section: Introductionmentioning
confidence: 99%